Towards a new administrative doctrine: governance and management for the 1990's - Hummel, Ralph P
Three successive terms of market-oriented presidents raise difficulties for federal bureaucrats in legitimating past administrative doctrine and practices, where were government-centered. The present article responds to Charles Levine's call for a new administrative doctrine that is more fully descriptive of the needs and routines of today's federal civil servants than adoctrine based on either a liberal or neo-conservative ideology. The author introduces the concept of doctrine into public administration discourse in order to clarify the differences in ideology, and practices between an era of top-down Liberal progressiuism and the era of bottom-up neo-sonservative progressivism that dawned with the first
Keywords: U.S.A; Public Administration